Perancangan Logo dan Desain Kemasan Produk Minuman Olahan Susu Merek Ibu Yudhi untuk Usia 6-12 Tahun dalam Upaya Meningkatkan Penjualan Produk di Sidoarjo - PP, Bintang Pramudya; Sukmaraga, Ayyub Anshari (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2023)
MSMEs in Indonesia cannot be underestimated. MSMEs can become the largest economy in Indonesia. For this reason, a high level of awareness is needed to have a brand or corporate identity to further develop it. Therefore it is necessary to make a logo and packaging design on the product as the company's identity. The aim is to differentiate between one product and another and to make companies from one product better known by the public. This study uses a qualitative method by collecting data through observation, interviews with company owners, and literature. Supporting media in this design are key chains, shopping bags, drawstring bags, small notes, stickers, drinking bottles, hats, displays, and pencil cases.